Global variants of COVID-19: Current understanding - Roy, B; Dhillon, JK; Habib, N; Pugazhandhi, B (Journal of Biomedical Sciences, 2021)
Background: SARS-CoV-2 is an RNA virus that undergoes mutation producing a variety of strains. Mutagens include UV radiation, metals, and endogenous components of organisms. Each strain is specific in terms of virulence, immune response in the body and efficacy of the vaccines. Conclusion: Researchers need to gather data and collaborate with global organizations to learn about the newly evolving strains. Information about the mutations and variants are inevitable in understanding virus transmission and developing vaccines to end the COVID-19 pandemic.